The Analysis of Turkish Foreign Policy in Syria: A Neoclassical Realist Perspective - Karaca, Bilal Bahadir; Köksal, Berk (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
Since 2011, the Syrian Civil War has become an arena of international competition between regional and global powers. As a dominant regional actor, Turkey has important interests in this conflict. However, although great importance is given to civil war factors and power balances at the field level, Turkey’s internal conditions play a role as well as these externalities. Therefore, an analysis of Turkey’s foreign policy towards Syria from a local perspective is needed to reveal some negligible dynamics. In this direction, this study aims to analyse Turkey’s foreign policy towards Syria, taking into account the interaction between Turkey’s external and internal dynamics within the framework of neoclassical realist theory. Within this scope, we ask “how do Turkish external and internal dynamics explain its foreign policy in Syria?” as the leading search question and conduct our analysis using the explanatory case study method. Based on our findings, we provide a broad perspective on the significant impacts of four main internal factors on Turkish foreign policy, from the start of the Civil War to the most recent “Operation Spring Shield” by the Turkish Army and local Syrian armed groups.

Od 2011 roku syryjska wojna domowa stała się areną międzynarodowej rywalizacji pomiędzy regionalnymi i globalnymi mocarstwami. Jako dominujący aktor regionalny, Turcja ma w tym konflikcie ważne interesy. Jednak, mimo że dużą wagę przywiązuje się do czynników wojny domowej oraz równowagi sił na poziomie międzynarodowym, to oprócz tych zewnętrznych uwarunkowań pewną rolę odgrywają również wewnętrzne uwarunkowania Turcji. Dlatego też potrzebna jest analiza polityki zagranicznej Turcji wobec Syrii z perspektywy lokalnej, aby ujawnić pewne pomijalne dynamiki. W tym kierunku, niniejsze opracowanie ma na celu analizę polityki zagranicznej Turcji wobec Syrii, biorąc pod uwagę interakcję pomiędzy zewnętrzną i wewnętrzną dynamiką Turcji w ramach neoklasycznej teorii realistycznej. W tym zakresie zadajemy pytanie „jak turecka dynamika zewnętrzna i wewnętrzna wyjaśniają jej politykę zagraniczną w Syrii?” jako wiodące pytanie poszukiwawcze i przeprowadzamy naszą analizę przy użyciu metody wyjaśniającego studium przypadku. W oparciu o nasze ustalenia przedstawiamy szeroką perspektywę znaczącego wpływu czterech głównych czynników wewnętrznych na turecką politykę zagraniczną, od początku wojny domowej do najnowszej „operacji Wiosenna Tarcza” prowadzonej przez armię turecką i lokalne syryjskie grupy zbrojne.
Analiza tureckiej polityki zagranicznej w Syrii: perspektywa realizmu neoklasycznego
Keywords: Syrian Civil War; Turkish Foreign Policy; Neoclassical Realism; Middle East; AKP; syryjska wojna domowa; turecka polityka zagraniczna; realizm neoklasyczny; Bliski Wschód; AKP